Educational leadership under construction: an experimental study on emotions and task performance using LEGO® bricks - Ventura, Mercedes; Ventura-Campos, Noelia (Frontiers in Education, 2025)
IntroductionThis study explored the impact of transformational and transactional leadership styles on emotional climate, task performance, and time perception in a university educational context. Additionally, it analyzed the evolution of emotional climate throughout a group activity focused on collaborative LEGO figure construction.MethodA quasi-experimental design was implemented with 93 university students divided into 23 groups. Each group completed two construction tasks under distinct leadership conditions: one focused on the final outcome (transactional) and the other on process facilitation (transformational). Emotional climate (positive and negative) was assessed at three time points (beginning, midpoint, and end), along with task performance, time perception, and qualitative reflections on the experience in both leadership conditions.ResultsThe findings showed that transformational leadership fostered a sustained increase in positive emotional climate, improved task performance, and greater satisfaction with the activity. In contrast, transactional leadership was associated with a progressive increase in negative emotions, lower construction accuracy, and higher perceptions of emotional discomfort. Qualitative responses reflected that in both cases the experiences were collaborative, motivating, and playful. However, under transformational leadership more positive emotions were experienced, whereas under transactional leadership, due to greater perceived difficulties in task execution, negative emotions such as frustration and stress increased.DiscussionThe results highlight the pedagogical value of transformational leadership in promoting positive emotional climates and effective collaborative learning environments. Its integration into teacher education programs is recommended as a strategy to enhance students' socioemotional wellbeing and academic engagement.